MITIGASI BENCANA DAERAH TUJUAN WISATA STUDI KASUS: PENTINGSARI, NGLANGGERAN, PENGLIPURAN - Setiawan Priatmoko; Yitno Purwoko; Anwani (Journal of Tourism Destination and Attraction, 2019)
The use of MSPDM analysis in community-based tourism (CBT) areas quite helpful. CBT helps stakeholders in planning the development of tourist areas in rural destination. For CBT areas that have implemented disaster mitigation, what has been done is in line with the parameters in the MSPDM analysis. CBT Nglanggeran and Pentingsari in Yogyakarta and Penglipuran in Bali have implemented several things that support disaster mitigation in its areas. The purpose of disaster mitigation is primarily to reduce the risk of disasters that occur to local residents and visitors. Disaster mitigation measures are carried out and adjusted to the characteristics of the local environmental and cultural area.